Transformasi Narko-Terorisme: Dari Kejahatan Ekonomi ke Ancaman Ideologis terhadap Kedaulatan Indonesia - Bimantoro, Tegar; Aris, Ardiyanti; Asriyani, Arini (Jurnal Litigasi Amsir, 2025)
The phenomenon of narco-terrorism illustrates the link between narcotics trafficking networks and terrorist groups that utilize the proceeds of economic crimes to fund ideological activities. This study aims to analyze the relationship between narcotics networks and terrorism networks in Indonesia, identify the funding strategies used, and assess their implications for national security. The study used a descriptive qualitative approach with an exploratory case study design in Gorontalo Province through in-depth interviews with key informants and analysis of official documents. The results show that narco-terrorism in Indonesia operates through loose, adaptive social-religious networks and exploits weaknesses in the legal system and correctional institutions. This phenomenon indicates a shift in the orientation of extremist groups from purely ideological to pragmatic, where narcotics trafficking is used as a strategic funding tool. Mitigation efforts must be cross-sectoral, with strengthening financial intelligence, reforming the correctional system, and increasing public awareness.